2018
DOI: 10.1088/1361-6528/aaa709
|View full text |Cite
|
Sign up to set email alerts
|

Micro-patterned graphene-based sensing skins for human physiological monitoring

Abstract: Ultrathin, flexible, conformal, and skin-like electronic transducers are emerging as promising candidates for noninvasive and nonintrusive human health monitoring. In this work, a wearable sensing membrane is developed by patterning a graphene-based solution onto ultrathin medical tape, which can then be attached to the skin for monitoring human physiological parameters and physical activity. Here, the sensor is validated for monitoring finger bending/movements and for recognizing hand motion patterns, thereby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…nanocomposite whose electrical conductivity is sensitive to applied strains was also designed, fabricated, and characterized. Its strain sensitivity was found to be ~ 10 times higher than films used in other studies 10,29,34 . Second, in order to overcome this limitation, a patterned nanocomposite was proposed to replace conventional continuous thin films.…”
Section: Significance Of the Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…nanocomposite whose electrical conductivity is sensitive to applied strains was also designed, fabricated, and characterized. Its strain sensitivity was found to be ~ 10 times higher than films used in other studies 10,29,34 . Second, in order to overcome this limitation, a patterned nanocomposite was proposed to replace conventional continuous thin films.…”
Section: Significance Of the Resultsmentioning
confidence: 61%
“…Several studies already showed that GNS could be integrated into polymer matrices to form high-performance strain sensors. [26][27][28][29] The GNS that was used in this work was synthesized using water-assisted liquid-phase exfoliation. The synthesis procedure was explained in detail in Manna et al 30,31 but is also summarized here for completeness.…”
Section: Nanocomposite Thin Film Preparationmentioning
confidence: 99%
“…Wearability could significantly increase the usage of haptics in our everyday life [44,45] . In the following paragraphs, we In previous studies, the haptic stimulation and physiological feedback system (HSPFS) has been prototyped to deliver the appropriate haptic cueing information, as well as to monitor the physiological signals [46,47] , and hence to improve the human performance in various applications such as (tele) rehabilitation [48,49] , industrial haptic design [50,51] and wearable sensing on psychophysiological states [52][53][54] . In one of the present studies, we built a haptic stimulation and digital signal to the microcontroller through SPI (i. e., Serial Peripheral Interface).…”
Section: Wearable Hapticsmentioning
confidence: 99%
“…[29] Such skin-mounted ultrathin nanocomposites can reliably capture finger-bending movements, [30] heartbeat and respiration, [31] and eye blinks and radial pulse. [32] Similarly, flexible tattoo-like sensors that integrated smart materials (e.g., polyvinylidene fluoride piezo-polymers or gold-silver nanocomposites) with serpentine-structured interconnects and skin-like medical tape have also been developed. [33][34][35] Another study has utilized a fish scale-like graphene-based sensing layer and demonstrated high sensitivity, stability, and broad sensing range for applications ranging from detecting vitals to monitoring joint-bending motions.…”
mentioning
confidence: 99%